On the genealogy of morals - Nietzsche, Friedrich (Arlington Richer Resources Publications, 2014)
Friedrich Nietzsche claimed that the purpose of On the Genealogy of Morals was to call attention to his previous writings. But in fact the book does much more than that, elucidating and expanding on the cryptic aphorisms of Beyond Good and Evil, and presenting a coherent discussion of morality in a work that is more accessible than much of his previous writings.
Includes index